(untitled) (Al-Qamar, 2021)
The Will has a significant part in Islamic law of succession. A major faction of Islamic jurists believes the Will as preferable. A few jurists consider it as obligation. Most important discussion in the context of Will is whether to bequeath in favor of heir or not. The majority of the jurists think of the will to be abrogated in favour of heir but Umar Ahmad Usmani, apart from populace verdict, presented different view about the issue in his book Fiqh al-Quran. This article consists of a critical analysis of his research work.